Catastrophes and Earth History : The New Uniformitarianism - Van Couvering, John A.; Berggren, William A. (Book collections on Project MUSE., 1984)
This book, based on papers from a symposium at the Woods Hole Oceanographic Institution, shows the necessity of developing a new philosophy in place of the classical uniformitarianism based only on processes familiar in human experience. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.